Specyfika pracy logopedycznej z wykorzystaniem elementów muzyki w pracy z dzieckiem autystycznym. Refleksje z praktyki = Specificity of logopedic therapy of children with autism with use of musical elements. Conclusions from practice - Mazur, Magdalena (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Music is a form of art people need, because they use it as a means of expression and creation of experiences and emotions, which enrich their lives. Music sharpens sensitivity, develops imagination, encourages independent thinking, and fulfils the need for self-expression. Music, with its multitude of forms, is being increasingly appreciated and harnessed in therapeutic processes.
Keywords: autyzm; zaburzenia rozwoju języka; słuch; komunikacja werbalna; komunikacja niewerbalna; diagnoza medyczna; głuchota; diagnoza surdologopedyczna; terapia neurologopedyczna; terapia surdologopedyczna; postępowanie terapeutyczne; autism; speech developmental disorders; hearing sense; verbal communication; non-verbal communication; medical diagnosis; hearing loss; diagnosis inspeech therapy for the hearing impaired; neurological speech therapy; therapy in speech therapy for the hearing impaired; therapeutic management